“What’s that?” “What Went Wrong?” Positive and Negative Surprise and the Rostral–Ventral to Caudal–Dorsal Functional Gradient in the Brain - Tops, Mattie; Boksem, Maarten A. (Frontiers in Psychology, 2012)
Medial prefrontal cortical (mPFC) functions may be aspects of ventral or dorsal control pathways, depending on the position along a rostral–ventral to caudal–dorsal gradient within medial cortex that may mirror the pattern of interconnections between cortex and striatum. Rostral–ventral mPFC is connected to ventral striatum and posterior cingulate cortex/precuneus are connected with dorsal striatum. Reentrant ventral (limbic), central (associative), and dorsal (motor) corticostriatal loops pass information from ventral-to-dorsal striatum, shifting hedonic processing toward habitual action. Splitting up unexpected occurrences (positive surprise) from non-occurrences (negative surprise) instead of splitting according to valence mirrors the importance of negative surprise in dorsal habitual control which is insensitive to the valence of outcomes. The importance of positive surprise and valence increases toward the rostral–ventral end of the gradient in mPFC and ventrolateral prefrontal cortex. We discuss paradigms that may help to disentangle positive from negative surprise. Moreover, we think that the framework of the functional gradient may help giving various functions in mPFC their place in a larger scheme.